PEMANFAATAN TEPIAN SUNGAI SEBAGAI BAGIAN DARI PENGEMBANGAN MANAJEMEN HOTEL PURI ASRI MAGELANG YANG BERBASIS EKOWISATA - Kristianto, Dwi Agus; Triyono, Joko (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2020)
This study aims to determine the use of riverbanks as part of the development of ecotourism-based hotel management at Hotel Puri Asri Magelang which includes planning, implementation, and evaluation as well as the obstacles faced in utilizing river banks at the hotel. The choice of Hotel Puri Asri Magelang was because the researchers viewed that this hotel was able to apply the concept of ecotourism well. This research is qualitative. The research method used is the method of interviewing, observation, and documentation. Analysis of the data used in this study using descriptive analysis. In a more comprehensive environmental impact analysis, socio-cultural and economic factors, the environment are also considered and in fact, it is often to try to separate the socio-economic and physical components of the environment, however, separate checks of these components are usually made as is done here, for convenience organization. Many features of the physical environment are attractions for tourists, tourism facilities and infrastructure are one aspect of the environment that is important in tourism activities. The development of tourism and the use of tourists in an area can have environmental impacts. The type and extent of environmental impacts are also closely related to the type and intensity of tourism development undertaken. Keywords: ecotourism, sustainable tourism development, hotel management